The Ornithological Importance Of The Amansuri Community Nature Reserve In The Western Region Of Ghana (Journal of Science and Technology, 2016)
This study was undertaken to establish the ornithological importance of the Amansuri Wetlands since birds are key bio-indicators, which are believed to provide information about the condition of, and alterations in the environment. Using standard survey techniques, the study has consolidated baseline information that can be used for future monitoring of avian species in the wetlands. A total of 128species belonging to families were recorded with 45% considered to be associated with mature forestsand 7.8% including Ardea goliath, Vanellus spinosus, Gallinula chloropus, Centropus leucogaster, Merops orientalis, Campethera nivosa, Coracina azurea, Stizorhina fraseri finchi, Macrosphenus concolor, and Trochocercus nitens being rare or uncommon. The diversity, composition, and relative abundance of avian species at the study site compares very well with that obtained in forest reserves in southern Ghana. A number of species (30%) restricted to the Guinea-Congo Forest Biome which are of conservation concern were recorded at the site, thus, qualifying it as an Important Bird Area (IBA),which will need to be protected. However, for the site to be more valuable and conservation efforts appreciated by local fringe communities, there is the need to adopt site actions that will maximise local benefits and impact positively on the lives of local people, which in turn would elicit local support for conserving the natural resources of the site. It is therefore recommended that local conservation actions be approached from a more adaptive and less intrusive strategies